Highlights for the Management of a Child with Hypertension - Mouin G. Seikaly (International Journal of Pediatrics)
Over the past several decades, childhood hypertension has undergone a considerable conceptual change, as hypertension is a predictor of future development of cardiovascular disease in adults. Childhood hypertension has distinctive features that distinguish it from hypertension in adults. Pediatric hypertension is often secondary. It is widely believed that therapeutic intervention at an early age favorably modifies the long-term outcome of hypertension. Despite its significance as a cause for morbidity, childhood hypertension is underdiagnosed and less studied with many basic issues remaining contentious.